Cardiovascular Risk and Comorbidities in Patients with Rosacea: A Systematic Review and Meta-analysis - Tsung-Yu Tsai; Ying-Yi Chiang; Yu-Chen Huang (Medical Journals Sweden, 2020)
The association between rosacea and cardiovascular disease remains controversial. A systematic review and meta-analysis of the literature, from inception to 15 February 2020, was performed to compare cardiovascular risk and comorbidities in individuals with and without rosacea. Twelve studies, involving 40,752 patients with rosacea, were included. Compared with controls, patients with rosacea had higher systolic blood pressure (standardized mean difference (SMD) 0.293, 95% confidence interval (CI) 0.054-0.532), diastolic blood pressure (SMD 0.309, 95% CI 0.003-0.615), total cholesterol (SMD 1.147, 95% CI 0.309-1.984), low-density lipoprotein (SMD 0.792, 95% CI 0.174-1.409), C-reactive protein (SMD 0.26, 95% CI 0.099-0.421), greater epicardial fat thickness (SMD 1.945, 95% CI 1.595-2.296), and higher incidence of hypertension (odds ratio (OR) 1.204, 95% CI 1.097-1.332) and insulin resistance (OR 2.338, 95% CI 1.187-4.605). This study reveals that patients with rosacea are predisposed to increased subclinical cardiovascular risk.